2018
DOI: 10.1186/s13068-018-1150-8
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the functional roles of Glu175 in the hyperthermostable xylanase XYL10C-ΔN through structural analysis and site-saturation mutagenesis

Abstract: BackgroundImproving the hydrolytic performance of hemicellulases to degrade lignocellulosic biomass is of considerable importance for second-generation biorefinery. Xylanase, as the crucial hemicellulase, must be thermostable and have high activity for its potential use in the bioethanol industry. To obtain excellent xylanase candidates, it is necessary to understand the structure–function relationships to provide a meaningful reference to improve the enzyme properties. This study aimed to investigate the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…The GH-11 xylanases are therefore preferred that are xylan specific and release the sugars in a controlled manner (Henrissat and Davies, 1997;Qing et al, 2010). GH-11 xylanase (XYL10C-N) supports this hypothesis that showed a synergistic effect with cellulose and generates the sugars by reducing the sugar-producing rate to reduce the xylan-induced obstacles (You et al, 2018). Partial utilization of LCB-generated sugars by native microorganisms is one of the limiting factors that could be overcome by developing recombinant strains that can transform the available sugar in an efficient manner (Aftab et al, 2018).…”
Section: Other Miscellaneous Applications Of Extremophilic Endoxylanasesmentioning
confidence: 78%
“…The GH-11 xylanases are therefore preferred that are xylan specific and release the sugars in a controlled manner (Henrissat and Davies, 1997;Qing et al, 2010). GH-11 xylanase (XYL10C-N) supports this hypothesis that showed a synergistic effect with cellulose and generates the sugars by reducing the sugar-producing rate to reduce the xylan-induced obstacles (You et al, 2018). Partial utilization of LCB-generated sugars by native microorganisms is one of the limiting factors that could be overcome by developing recombinant strains that can transform the available sugar in an efficient manner (Aftab et al, 2018).…”
Section: Other Miscellaneous Applications Of Extremophilic Endoxylanasesmentioning
confidence: 78%
“…The catalytic domains of XylE and thermophilic XYL10C share 53% sequence identity (Additional file 1: Figure S1), and their crystal structures showed a common (α/β) 8 -barrel fold of GH10 xylanases [22, 23]. Two standards were used to determine the demarcation point of the sequences: (1) Each sequence retains the local secondary structure and (2) except for the N- and C-terminal sequences, each sequence has a length of less than 20 amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into the structural features responsible for the functional properties of ScXynA, we built a homology model. It should be noted that structures for eukaryotic GH10 xylanases are available in complex with xylobiose or xylotriose only [44,68], while bacterial xylanases are represented by inactive mutants complexed with oligosaccharides of DP up to 7, and provide a better overview of a binding cleft. A brief phylogenetic analysis of xylanase GH10 sequences available in PDB showed that ScXynA is closely related to some bacterial xylanases ( Figure S3).…”
Section: Discussionmentioning
confidence: 99%